PENGARUH CUACA TERHADAP KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KABUPATEN NGANJUK - Tutut Pujianto (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2016)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus andinfected by mosquitoes Aedhesaegypti. Incidence of dengue affected by the weather conditions of the mosquito habitat itself. By using the data of dengue incidence of East Java Health Office and weather conditions from BMKG of SawahanNganjuk in 2010-2014, can be performed to determine the influence of weather forecasting (X) ((temperature (X1), rainfall (X2), solar radiation (X3), humidity (X4), and wind speed (X5) on the incidence of DHF (Y). The results of linear regression analysis with SPSS software (α: 0.05) in Genesis models get dengue=0.106 -1.943 rain moisture. From that model it is known that rainfall is the dominant factor affecting the incidence of dengue. Therefore, efforts should be made for preventing the incidence of DHF is doing the cleaning continer before the rains come.